Self Control Pada Anak Abk Di SLB Negeri Jember - Sulaima, Izzatus; Khamidah, Dian Alfi; Rohmaniyah, Hanik Endah; Fitriana, Ani Qotuz Zuhro’ (Jurnal Ilmu Sosial, Humaniora dan Seni, 2022)
This study aims to determine self-control in children with special needs in the country of Jember, this study also aims to determine the role of teachers in increasing the self-control of children with special needs with some disabilities such as children who are deaf and blind, analyze the programs given and strategies, supporting factors and program inhibitors, as well as evaluation of programs to increase self-control in children with special needs outside Jember. This study used a qualitative descriptive approach, by taking a background in SLB Negeri Jember, data collection techniques were carried out by carrying out observations, interviews and documentation and the subjects in this study were 5 people. The results showed that the factors that influence the process of increasing self-control are cooperation and willingness between students and teachers to develop self-control in children who have different features.